Quality‐of‐life impact after in‐office treatment of nasal valve obstruction with a radiofrequency device: 2‐year results from a multicenter, prospective clinical trial. Issue 4 (9th August 2020) - Ephrat, Moshe; Jacobowitz, Ofer; Driver, Mark
Abstract : Background: Insufficiency of the nasal valve is increasingly being recognized as a cause of nasal airway obstruction. The condition is associated with many symptoms, including nasal congestion, sleep disturbance, snoring, and an overall decline in quality of life (QoL). An in‐office, minimally invasive radiofrequency treatment of the nasal valve has been associated with improved symptoms of nasal obstruction and patients' QoL for a 6‐month period in a noncontrolled, prospective, single‐arm study. The purpose of this study was to determine whether the results achieved with radiofrequency treatment at 6 months would be sustained through 24 months. Methods: Thirty‐nine adult patients from an original cohort of 49 patients with severe to extreme Nasal Obstruction Symptom Evaluation (NOSE) Scale scores and dynamic or static internal nasal valve obstruction as the primary or significant contributor to obstruction were studied. Patients received intranasal bilateral radiofrequency treatment in a clinical study with a follow‐up to 6 months, and were prospectively evaluated at 12, 18, and 24 months at 8 community‐based otolaryngology practices. The patient‐reported NOSE Scale score and 21 QoL questions were assessed. Results: Clinically significant improvement from baseline in NOSE Scale score change demonstrated at 6 months (mean, 55.9; standard deviation [SD], 23.6; p < 0.0001) was maintained through 24 months (mean, 53.5; SD, 24.6; p < 0.0001). Responders (≥15‐point improvement) consisted of 92.3% of participants at 6 months and 97.2% at 24 months. Responses to the QoL questions also showed improvement in patients' QoL. Conclusion: Treatment of the nasal valve with an in‐office, transnasal temperature‐controlled radiofrequency procedure was associated with stable and lasting improvement in symptoms of nasal obstruction and QoL through 24 months in this noncontrolled, single‐arm study.